(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Power requirements of the world are ever increasing. In order to fulfill these, it is essential to discover new energy sources or rather improvise the existing techniques for extracting maximum energy. The Wind tree is a concept that uses a helical blade (VAWT) for generation of electric power. The helical blade is Omni-directional which means it is capable of rotating irrespective of the wind flow. The project aims at generating electricity by means of small wafts of air that circulate around the buildings and streets. Despite of the wind being fluctuating in nature; the turbine is capable of generating electricity, as a small waft of air is sufficient to rotate this turbine.